Correlation between obstructive sleep apnea and weight-adjusted-waist index: a cross-sectional study - Zhang, Mengye; Weng, Xiaolu; Xu, Jing; Xu, Xue (Frontiers in Medicine, 2024)
Background: Obesity is recognized as a prominent factor in the pathogenesis of obstructive sleep apnea (OSA). The weight-adjusted-waist index (WWI) has emerged as a novel metric for assessing adiposity. The study aimed to investigate the potential correlation between WWI and OSA. Methods: In this study, a cross-sectional analysis was conducted on the data from the National Health and Nutrition Examination Survey (NHANES) during the period from 2013 to 2020. To examine the correlation between WWI and OSA, multivariate logistic regression, smooth curve fitting, subgroup analysis and receiver operating characteristic (ROC) curve were employed. Results: Among the total 18,080 participants, 9,050 were categorized as having OSA. It was observed that as the quartile range of WWI increased, there was a gradual rise in the prevalence of OSA (37.4% vs. 50.3% vs. 55.1% vs. 57.5%, p<0.001). Logistic regression analyses demonstrated a significant positive correlation between WWI and the risk of OSA, even after accounting for potential confounders (OR=1.314, 95%=1.223, 1.411). Subgroup analysis further revealed a stronger correlation between OSA and WWI among individuals with normal weight, those under 50 years old, and those engaging in moderate physical activities. Smooth curve fitting identified a positive non-linear correlation, with an inflection point at 11.678. ROC analysis indicated that WWI (AUC=0.664) can serve as a more robust predictor for OSA compared to BMI and waist circumference. Conclusion: This study provides evidence that elevated levels of WWI are correlated with an increased risk of OSA, indicating the potential utility as predictive indicators for OSA